Technology innovation smart jewelry, Lumiére Armilla - Zahari, Muhammad Haikal; Abu Bakar, Norida; Mohd Shahril, Nur Aqilah Darwisyah; Zainal Abidin, Nur Annisa Fatiha; Muhammad Aliff Taufiq, Nor Fazira; Sarojin, Syaza Aliya Nazihah; Haris Faizal, Ardini Syahirah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
In a world where communication is an essential part of our daily life, the hurdles from linguistic gaps present a major obstacle, especially for the individuals who are unable to speak and who use sign language as their primary mode of communication. This abstract outline of “Lumiere Armilla”, a wearable technology that combines fashion and accessibility, to help aid individuals who are having difficulties in speaking. The jewelry set by Lumiere Armilla helps in conveying words that could not be said. Furthermore, the jewelry has an added flex sensor technology which aids in interpreting the sign language gesture with audio to help understand the wearer. The jewelry is also equipped with simple touch screen controls and an audio adjuster. To sum it up, Lumiére Armilla can help in giving light to those who cannot speak and help them achieve independence and gain self-empowerment.